2018
DOI: 10.1055/s-0038-1667078
|View full text |Cite
|
Sign up to set email alerts
|

As Ontologies Reach Maturity, Artificial Intelligence Starts Being Fully Efficient: Findings from the Section on Knowledge Representation and Management for the Yearbook 2018

Abstract: Ontologies are demonstrating their maturity to integrate medical data and begin to support clinical practices. New challenges have emerged: the query on distributed semantically annotated datasets, the efficiency of semantic annotation processes, the semantic representation of large textual datasets, the control of biases associated with semantic annotations, and the computation of Bayesian indicators on data annotated with ontologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In direct line with the research presented last year 1 , the 2018 four best papers demonstrated even further the added-value of ontology-based integration approaches for phenotype-genotype association mining.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…In direct line with the research presented last year 1 , the 2018 four best papers demonstrated even further the added-value of ontology-based integration approaches for phenotype-genotype association mining.…”
Section: Resultssupporting
confidence: 55%
“…We conducted the selection of KRM papers based on a new set of queries. In comparison with the previous editions of the IMIA Yearbook, both PubMed/MELDINE and Web of Knowledge were used to search for KRM articles published in 2018 1 . We followed the generic method commonly used in all sections of the Yearbook to select the best papers.…”
Section: Paper Selection Methodsmentioning
confidence: 99%
“…We conducted the selection of KRM papers based on the set of queries established in the 2019 edition of the IMIA Yearbook of Medical Informatics 1 . As compared with the previous editions of the IMIA Yearbook in 2017 and 2018 2 3 , both PubMed/MELDINE and Web of Knowledge were used to search for KRM articles published in 2019. We followed a generic method to select the best papers, commonly used in all sections of the Yearbook since 2013 [].…”
Section: Paper Selection Methodsmentioning
confidence: 99%
“…We conducted the selection of KRM papers, based on the set of queries optimized during the last editions of the International Medical Informatics (IMIA) Yearbook [ 1 2 3 4 ]. In comparison with the latest editions of the IMIA Yearbook [ 3 , 4 ], where both PubMed/MELDINE and Web of Science™ were used to search for KRM articles, we did not expand the search to the Web of Science (WoS) database this year.…”
Section: Paper Selection Methodsmentioning
confidence: 99%